Soybean Cost-Return Budget in Southeast Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2010)
This publication outlines the expected costs and returns for soybean production in southeast Kansas.
MF994_2010_11
Keywords: MF994; Economics; Crops; MF